Translational Research Grants Scheme (TRGS): a new approach to strengthening health system research capacity - Robin Auld; Tina Loppacher; Shiho Rose; Andrew J Milat; Antonio Penna (Sax Institute, 2018)
Background: Bridging the 'gap' between research evidence and the complexities of policy and practice is central to health improvement. The Translational Research Grants Scheme (TRGS) in New South Wales (NSW), Australia, is a funding scheme aimed at reducing the time between research generation and translation to policy and practice. The TRGS is also an important part of NSW Health's efforts to harness and strengthen research capacity to improve health service delivery. Methods: A document review and interviews (n = 12) with key stakeholders were undertaken following the first round of TRGS funding in November 2016. The communications from continuing quality improvement processes over the three funding rounds have provided further insight. Results and discussion: A total of 53 projects have been funded under the scheme, with recipients across many NSW Health organisations. NSW Health has committed more than $24 million to date. Round one of the TRGS was received well by the policy makers, Local Health Districts and research stakeholders interviewed. Of particular note were: the requirement for Chief Executives to demonstrate strong support for the implementation of findings; requirements to partner with state-wide policy leads and clinical networks; and capacity-building outcomes of the scheme. The ongoing quality improvement processes indicate that the program continues to be well received, with improvements to partnership arrangements, and an acknowledgement of the challenge that arises because the scheme, by nature of its capacity-building aim, attracts proposals from a range of research experience. Lessons learnt: The TRGS is filling an important gap in the research funding landscape in NSW and is well regarded by stakeholders. To ensure that the TRGS is achieving its intended aims, an evaluation of the impact of the scheme will take place during 2018-19.